Síntese de (E)-1-bromo-1-arilselenoalquenos e arilselenocetenocetais a partir de 1,1-dibromoalquenos - Webber, Rodrigo (2016)
In this work, a metal-free methodology was developed by reaction between diaryl diselenides 1 and 1,1-dibromo-alkenes 2 to synthesize (E)-1- bromo-1-selenoalkenes 3 and ketene selenoacetals 4. The protocols employed a diverse array of nucleophilic selenium species, generated in situ from the corresponding diaryl diselenides 1 using sodium borohydride (NaBH4) as a reducing agent in polyethylene glycol-400 (PEG-400) as solvent and differently substituted 1,1-dibromoalkenes 2. The compounds 3 and 4 were selectively obtained by simple stoichiometry and temperature-controlling reaction. When 1 equiv. of diaryl diselenides 1 were used, nine (E)-1-bromo-1-seleno alkenes 3 were formed in good yields (49-95%) at 50 °C using conventional heating over a reaction period of 0.5 to 2.0 h. On the other hand, when 2.2 equiv. of diaryl diselenides 1 were used at 120 °C, five ketene selenoacetals 4 were efficiently obtained in a range of 42% to 76% yield, over a period of 1.0 to 3.5 h.